Cecropin anisaxin-2S has in vitro immunomodulatory, but not antiproliferative and antiviral properties - Majstorović, Jovana; Arakelyan, Anush; Trumbić, Željka; Kamiš, Jan; Adamek, Mikolaj; Rončević, Tomislav; Čikeš Čulić, Vedrana; Kyslík, Jiří; Palus, Martin; Fiala, Ivan; Mladineo, Ivona (Frontiers in Immunology, 2025)
Helminthic host defense peptides (HDP) are pleiotropic, multifunctional effector molecules of helminth immunity, efficient against Gram-negative and Gram-positive bacteria. Among them, anisaxin-2S (A-2S), membranolytic cecropin-like HDPs produced by the zoonotic nematodes of the genus Anisakis, shows remarkable efficacy even against multidrug-resistant Gram-negative bacteria, yet its immunomodulatory, antiproliferative and antiviral properties have not been elucidated. Therefore, we tested A-2S immunomodulation in the common carp (Cyprinus carpio) blood cells exposed to two pathogens, the zoonotic bacterium Aeromonas hydrophila and the fish parasite Sphaerospora molnari, and in carp in vivo challenged with the parasite. Furthermore, the A-2S antiproliferative activity was tested in vitro in human bladder and lung cancer cell line, while the antiviral protection was tested in common carp brain cell culture exposed to carp rhabdovirus, alloherpesvirus and paramyxovirus, and in a human immortalized myelogenous leukemia cell line infected with tick-borne encephalitis virus. A-2S exerts an immunostimulatory effect on fish blood cells through upregulation of cytokine expression, with the proinflammatory or anti-inflammatory repertoire conditioned by the presence or absence of co-stimulatory antigen. Surprisingly, in the majority of assays conducted, red blood cells demonstrate equal or even stronger regulation of innate immunity genes compared to white blood cells, along with a more extensive repertoire of differentially expressed markers. In contrast, A-2S has only a limited anticancer activity in human bladder cancer and lung adenocarcinoma cells and limited antiviral activity against the three fish viruses and a human tick-borne encephalitis virus. This study provides the first evidence of red blood cell and platelet immunomodulation by an antimicrobial peptide and highlights the induction of a cytokine repertoire. However, future research should address the study’s limitations, including the need for longer in vitro assays (e.g., 3–4 days), testing different white blood cell lineages, to better understand antigen-processing interactions, and evaluating the anticipated adaptive immune response. Powerful antimicrobial activity of A-2S, coupled with immunostimulatory properties, warrant further pursuing of preclinical trials with this anisaxin.